A Novel approach Secure Routing in Wireless Sensor Networks for Safe Path Establishment of Private IoT Data Transmission - Shanthi, T.; Sheela, M. Sahaya; Jayakanth, J. J.; Karpagam, M.; Srividhya, G.; Prasad, T. V. S. Gowtham (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Internet of Things relies on wireless sensor networks (WSNs) to gather data and transmit it to centralized databases. Most of the power used by these sensors goes toward detecting or collecting and delivering the data because they run on batteries and have limited resources. Wormhole attacks are the most devastating threat that may befall these networks, making data security a top priority throughout data exchange. The communication, security, and performance of the network are severely compromised by these assaults since they are launched without first gathering essential information. Due to limited resources in sensors, it is more difficult to prevent in an IoT-based network environment. If an unwanted node is present in the system, it will slow everything down. In order to keep malicious software and hacking attempts out of WSNs, secure routing protocols must be implemented. Since security is paramount in WSN, several different safe routing protocols have been created to enhance the efficiency with which packets may be sent. Using the multipath link routing protocol along with improved blow fish model (MLRP-IBFM), our proposed strategy creates a safe path for private IoT data to travel between sensor nodes with varying levels of available power. Data transfer rates, power consumption, latency from beginning to finish, system lifespan, and information storage space are only few of the performance metrics where this routing protocol excels when compared to two other current routing protocols.